Effect of Ease of Use and Consumer Experience on Repurchase Intention of Train Tickets Through Kai Access With Satisfaction as a Mediation Variable: Study on Kai Access Users in Malang - Elisa; Agung Winarno; Titis Shinta Dewi (Economics and Business Journal (ECBIS), 2023)
Along with the increasing competition in the world of transportation business which is getting tighter, ease of use and consumer experience is an effective marketing strategy in providing service and satisfaction to many consumers and this can encourage consumer repurchase interest. The purpose of this study is to determine the effect of ease of use and consumer experience on repurchase intention through satisfaction. The population in this study are consumers who know the KAI Access application in the city of Malang. While the sample in this study was 271 respondents. This type of research is descriptive and non-probability, using the Smart PLS program. The results are (1) ease of use has a positive and significant effect on satisfaction (2) consumer experience has a positive and significant effect on satisfaction (3) ease of use has a positive and significant effect on repurchase intention (4) consumer experience has a positive and significant effect on repurchase intention (5) satisfaction has a positive and significant effect on repurchase intention (6) ease of use has a positive and significant effect on repurchase intention through satisfaction (7) consumer experience has a positive and significant effect on repurchase intention through satisfaction. Based on the results of the study, similar business actors suggest that companies are more selective in using ease of use which will provide a good experience for consumers so that consumers feel satisfied and feel an interest in repurchasing